2018
DOI: 10.1177/1708538118756690
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral artery disease is associated with frailty in chronic hemodialysis patients

Abstract: Objectives The clinical condition of frailty is a common problem in the elderly population. However, the relationship between peripheral artery disease and frailty in hemodialysis patients remains unknown. The aim of this study was to identify the relationships between peripheral artery disease and frailty in Japanese chronic hemodialysis patients. Methods A total of 362 chronic hemodialysis patients who regularly visited six institutions were enrolled. To evaluate frailty, the modified Fried's frailty phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Regarding the complication of DM, the authors reported that peripheral artery disease was closely associated with frailty in chronic HD patients. 10 It is well known that DM is strongly related to peripheral artery disease. 11,27 As expected, in the present study, the ABI score was lower in the DN group than the Non-DN group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the complication of DM, the authors reported that peripheral artery disease was closely associated with frailty in chronic HD patients. 10 It is well known that DM is strongly related to peripheral artery disease. 11,27 As expected, in the present study, the ABI score was lower in the DN group than the Non-DN group.…”
Section: Discussionmentioning
confidence: 99%
“…The initial exclusion criteria were: (i) patients who refused to participate; (ii) patients who were in a hospital due to accidents or sickness; and (iii) patients who were unable to answer the questionnaire. In addition, the authors excluded participants who did not completely fill in the frailty information, as the authors described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the previous study included few patients with severe CKD on hemodialysis. A recent cross‐sectional study in a cohort of patients receiving hemodialysis demonstrated a significant association between PAD and frailty as defined by Fried's frailty phenotype modified for the Japanese population 14 . However, since this previous study examined only the association between PAD and a medical syndrome (i.e., frailty) in which the five components were unclear, detailed data on the relationships between PAD and physical function and physical activity were lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross-sectional study in a cohort of patients receiving hemodialysis demonstrated a significant association between PAD and frailty as defined by Fried's frailty phenotype modified for the Japanese population. 14 However, since this previous study examined only the association between PAD and a medical syndrome (i.e., frailty) in which the five components were unclear, detailed data on the relationships between PAD and physical function and physical activity were lacking. For disease management (intervention), it is necessary to clarify not only the medical symptoms but also the relationship with physical functions.…”
Section: Introductionmentioning
confidence: 99%